Iraqi EFL Students’ Perceptions Towards Entertainment And Rigorous Learning (Journal of Humanities and Social Sciences Research, 2023)
This study aims to investigate Iraqi students’ perceptions towards entertainment and rigorous learning at the College of Education for the woman/university of Tikrit. Educational computer game research expanded rapidly as a result of the widespread perception among younger generations that games might provide several educational advantages. It is useful to understand how educational games can help strengthen the engagement and learning perceptions of our students towards technology in the light of intensive teaching activities and the actions of teachers to build a respectful, constructive learning atmosphere for the conduct of students towards each other and the rate and level of involvement of students in class discussion. The tool of the study is a questionnaire checklist from strongly agree to disagree strongly. The sample of the study consists of 82 (female) participants at the English department/university of Tikrit. This paper investigates two aspects of learning and comprehensive learning for educational games. The results demonstrated that the majority of students were more motivated to learn programming through the use of games than through traditional methods, fostering hopeful attitudes. Hopefully, the results would serve to enrich information in recognizing the attitudes of students about educational learning games, with the outcome of the exchange for rigorous learning revealing that students have negative perceptions about several points that respect teachers for students, weak cooperative work, and guidelines for respect during class conduct.